Do útero à adoção: a experiência de mulheres férteis que adotaram uma criança - Maux, Ana Andréa Barbosa (2008)
Even with all changes and ruptures related to the social roles that woman had performed, the literature had confirmed that the motherhood still configures it like one of the main roles that she hopes to play in some moment of her life. When the woman did not get pregnant or take ahead a pregnancy, some women find in adoption an alternative to play this role. This research aimed to understand the experience of being mother for adoption in the case of fertile women, but whose partner is infertile. Supported by existential-phenomenological theory, used it the narrative, how methodological instrument. Participated five women, whose adoption process followed the legal ways in the Youngness and Infancy Judgeship of Natal/RN. The results showed that in the selfish training, the woman to see herself how whose role principal is to generate children, although, she think that is natural her participation in others activities go out home too. In male infertile case is a tendency that the woman strikes the infertile status too. The adoption is an alternative to fulfill her desire of being a mother and, meanwhile, please her husband and guarantee the continuity of her love relationship. Through motherly care, the woman discover herself as a mother, what brings a new meaning for her live, independent of to generate a child. Though, exit frustration, sometimes, in association with suffering, on account of the pregnancy and childbirth absence. The end of the research suggests reflections that to become fulfilled herself as mother, the woman does not need, necessarily, to generate a child, being the maternity one of the uncountable possibilities that are shown, and that she can choose, or not, accomplish it